Epigenetic Changes and Transcriptional Reprogramming Upon Woody Plant Grafting for Crop Sustainability in a Changing Environment - Kapazoglou, Aliki; Tani, Eleni; Avramidou, Evangelia V.; Abraham, Eleni M.; Gerakari, Maria; Megariti, Stamatia; Doupis, Georgios; Doulis, Andreas G. (Frontiers in Plant Science, 2021)
Plant grafting is an ancient agricultural practice widely employed in crops such as woody fruit trees, grapes and vegetables, in order to improve plant performance. Successful grafting requires the interaction of compatible scion and rootstock genotypes. This involves an intricate network of molecular mechanisms operating at the graft junction and associated with the development and the physiology of the scion, ultimately leading to improved agricultural characteristics such as fruit quality and increased tolerance/resistance to abiotic and biotic factors. Bidirectional transfer of molecular signals such as hormones, nutrients, proteins and nucleic acids from the rootstock to the scion and vice versa have been well documented. In recent years, studies on rootstock-scion interactions have proposed the existence of an epigenetic component in grafting reactions. Epigenetic changes such as DNA methylation, histone modification and the action of small RNA molecules are known to modulate chromatin architecture, leading to gene expression changes and impacting cellular function. Mobile small RNAs (siRNAs) migrating across the graft union from the rootstock to the scion and vice versa mediate modifications in the DNA methylation pattern of the recipient partner, leading to altered chromatin structure and transcriptional reprogramming. Moreover, graft-induced DNA methylation changes and gene expression shifts in the scion have been associated with variations in graft performance. If these changes are heritable they can lead to stably altered phenotypes and affect important agricultural traits, making grafting an alternative to breeding for the production of superior plants with improved traits. However, most reviews on the molecular mechanisms underlying this process comprise studies related to vegetable grafting. In this review we will provide a comprehensive presentation of the current knowledge on the epigenetic changes and transcriptional reprogramming associated with the rootstock–scion interaction focusing on woody plant species, including the recent findings arising from the employment of advanced –omics technologies as well as transgrafting methodologies and their potential exploitation for generating superior quality grafts in woody species. Furthermore, will discuss graft–induced heritable epigenetic changes leading to novel plant phenotypes and their implication to woody crop improvement for yield, quality and stress resilience, within the context of climate change.